Active nuclear transcriptome analysis reveals inflammasome-dependent mechanism for early neutrophil response to Mycobacterium marinum - Kenyon, Amy; Gavriouchkina, Daria; Zorman, Jernej; Napolitani, Giorgio; Cerundolo, Vincenzo; Sauka-Spengler, Tatjana (Scientific reports, 2017)
The mechanisms governing neutrophil response to Mycobacterium tuberculosis remain poorly understood. In this study we utilise biotagging, a novel genome-wide profiling approach based on cell type-specific in vivo biotinylation in zebrafish to analyse the initial response of neutrophils to Mycobacterium marinum , a close genetic relative of M . tuberculosis used to model tuberculosis. Differential expression analysis following nuclear RNA-seq of neutrophil active transcriptomes reveals a significant upregulation in both damage-sensing and effector components of the inflammasome, including caspase b , NLRC3 ortholog ( wu: fb15h11 ) and il1β . Crispr/Cas9-mediated knockout of caspase b , which acts by proteolytic processing of il1β, results in increased bacterial burden and less infiltration of macrophages to sites of mycobacterial infection, thus impairing granuloma development. We also show that a number of immediate early response genes (IEGs) are responsible for orchestrating the initial neutrophil response to mycobacterial infection. Further perturbation of the IEGs exposes egr3 as a key transcriptional regulator controlling il1β transcription.